Smart mattress integrated with pressure sensor and IoT functions for sleep apnea detection. (December 2022) - Sangeetha, T.; Kumutha, D.; Bharathi, M. Divya; Surendran, R.
Abstract: Obstructive Sleep Apnea (OSA) is the main reason for sleep-associated respiration disorders, wherein respiration stops and begins evolved again and again at some pointing sleep. Sleep-disordered respiration can affect our common health protection and quality of life. This look targets at detecting sleep posture and sleep-disordered respiration through measuring the sensory reaction of a pressure sensor and respiration microphone sensor set up with mattresses, pillowcases, and positional sleep apnea. Three positions use of pressure sensors were used to analyze. The respiration microphone sensor is used for the duration of sleep and to measure breathing levels. In this work, we have got an advanced sleep monitoring system based on an inattentive method. Internet of Things (IoT) is used to transmit information saved in sensors and displayed in internet applications. Helps us without problems displaying gold coins and gold time periods.